A104 PREGNANCY OUTCOMES IN WOMEN WITH INFLAMMATORY BOWEL DISEASE AND EXPOSURE TO BIOLOGICS - A PROSPECTIVE COHORT STUDY. (1st March 2018) - Wang, S; Pena-Sanchez, J; Fowler, S
Abstract: Background: Inflammatory bowel disease (IBD) has a peak incidence rate in women of reproductive age. Biologic agents are commonly used in IBD management. However, prospective safety data on biologics exposure in the pregnant population remain limited. Aims: To assess baseline differences, and to compare obstetrical and neonatal outcomes in women with IBD who are exposed and non-exposed to biologics during pregnancy. Methods: Since November 2014, pregnant women with ulcerative colitis (UC) or Crohn's disease (CD) were enrolled in a prospective registry. Patients were assessed every trimester, and at three, six, and 12-months post-partum. Disease activity, pregnancy complications, and delivery and newborn outcomes were recorded. Women were divided into exposed (adalimumab [ADA], infliximab [IFX], vedolizumab [VDZ], or ustekinumab [UST]) and non-exposed (no medications or 5-aminosalicylic acid [5-ASA]) groups. Patients taking only immunomodulators were excluded. Mann–Whitney U and Fisher's exact tests were used to identify differences between groups. Results: To date, 36 patients have been enrolled in the study, totalling 38 pregnancy events. Sixteen pregnancy events were exposed to biologics: 9 (56.2%) ADA, 4 (25.0%) IFX, 2 (12.5%) VDZ, 1 (6.2%) UST. Twenty-two pregnancy events were not exposed: 8 (36.4%) 5-ASAs and 14 (64.6%) no medications. Within the exposed and non-exposed groups, 13 (81.3%) and 14 (63.6%) women had CD, respectively. The exposed group had fewer patients with a smoking history (1 [6.3%] vs 11 [50.0%], p=0.04), while a higher proportion had an annual household income above $100, 000 (11 [78.6%] vs 7 [35.0%], p=0.012). No differences were observed between groups for adverse pregnancy diagnoses (gestational hypertension and diabetes, preeclampsia/eclampsia), post-partum infections, and neonatal outcomes (low birth weight, prematurity, and infections). Disease relapse during pregnancy (5 [31.3%] vs 8 [36.4%], p=0.74) and steroid use (4 [25%] vs 3 [13.6%], p=0.42) were similar between exposed and non-exposed groups, respectively. Caesarian section (CS) occurred in 7 (46.7%) of exposed and 10 (62.5%) of non-exposed group (p=0.38), while 6 (16.7%) patients in total had active perianal disease. There was a trend towards significance for increased emergency CS within the non-exposed (6 [37.5%]) compared to exposed group (1 [6.7%], p=0.08). No significant difference was observed for breast feeding rates between groups. Conclusions: Biologics exposure does not appear to be associated with adverse pregnancy and neonatal outcomes. Higher socioeconomic status was linked to women using biologics during pregnancy. A high CS rate was also observed overall while few had an IBD-related indication. Future studies should explore any barriers to accessing biologics in Canada, and the propensity for CS in women with IBD. Funding Agencies: Saskatchewan Health Research Foundation (SHRF)